Manufacturing and novel applications of multilayer polymer films - Langhe, Deepak; Ponting, Michael (PDL handbook series., 2016)
Manufacturing and Novel Applications of Multilayer Polymer Films discusses the advancements in multilayer technology, including its capability to produce hundreds of layers in a single film by a melt coextrusion process. These engineered films can have significantly enhanced performance properties, allowing films to be made thinner, stronger, and with better sealing properties. As recent developments in feedblocks and materials have opened up a range of new possibilities, this book discusses different feedblocks, and viscosity and material considerations. It is the first comprehensive summary of the latest technology in multilayer film processing and related applications, and is written from a practical perspective, translating research into commercial production and real world products. The book provides fundamental knowledge on microlayer coextrusion processing technology, how to fabricate such structures, structure and properties of such microlayers, and potential applications, thus helping research scientists and engineers develop products which not only fulfill their primary function, but can also be manufactured reliably, safely, and economically.